Value Education Model in the Formation of Student Character at the State Islamic Universities in Indonesia - Rifda El Fiah , Syaiful Anwar and Nilawati Tadjuddin (International Journal of Advanced Science and Technology, 2020)
Value education in the formation of student character in campus is a central issue thatis very relevant and actual considering the campus as an institution of higher educationthat has the authority and capability in building and delivering quality of humanresources and character. This study takes the theme of the Value Education Model in theFormation of Student Characteristics in three UINs in Indonesia (UIN SyarifHidayatullah Jakarta, UIN Sunan Gunung Djati Bandung, and UIN Raden IntanLampung). From the research findings, the following findings were obtained: 1. Themodel of value education in the formation of student character carried out in three UINsin Indonesia: (a) classroom learning activities by lecturers, (b) through the activity unit ofthree student fields and cooperation involving student units (DEMA SEMA, and UKMs),(c) through the creation of a conducive environment (comfortable, clean, and safeatmosphere). As for the characters that emerge from the results of coaching conducted tostudents show the following results: (a) dynamic leadership character, (b) entrepreneurialcharacter, (c) independence character, (d) discipline character, (e) cleanliness/neatnesscharacter, and (f) religiosity character (Islamic). This research also found an offer of amodel of value education in shaping the character of students on campus that can beapplied in other tertiary institutions, namely achieving the vision and mission of theprogram and the expected targets.